2013
DOI: 10.1097/01.sa.0000425538.49851.a1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nitrous Oxide Exposure During Surgery on the Homocysteine Concentrations of Children

Abstract: In this study we determined the effect of nitrous oxide (N 2 O) on homocysteine concentrations in children and whether blood levels of folate, vitamin B12, B6, methylmalonic acid (MMA) and methylenetetrahydrofolate reductase C6777T genotype affected this relationship. Homocysteine was measured before and after N 2 O. Vitamin levels, MMA and genotype were determined preoperatively. Median age of the 32 participants was 11 months (3-126 months). All children had folate and B6 levels above deficiency values (7.4,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 154 publications
(245 reference statements)
1
9
1
Order By: Relevance
“…Exposure to nitrous oxide causes a moderate increase in the tone of the sympathetic system with subsequent moderate vasoconstriction of the splanchnic vascular system leading to a reduction in v. portae blood flow and moderate vasoconstriction of the hepatic arterial system. As mentioned above, nitrous oxide is known as an inhibitor of the enzyme methionine synthetase in the liver, so long-term exposure can lead to toxic hepatic effects [ 16 - 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to nitrous oxide causes a moderate increase in the tone of the sympathetic system with subsequent moderate vasoconstriction of the splanchnic vascular system leading to a reduction in v. portae blood flow and moderate vasoconstriction of the hepatic arterial system. As mentioned above, nitrous oxide is known as an inhibitor of the enzyme methionine synthetase in the liver, so long-term exposure can lead to toxic hepatic effects [ 16 - 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…20 Also, many case studies have shown subacute combined degeneration after nitrous oxide anesthesia. [21][22][23] Pichardo et al 24 evaluated children undergoing plastic surgery. Similar to our findings, they reported that nitrous oxide anesthesia for longer than two hours significantly increased serum homocysteine levels during the first 24 hours after the surgery.…”
Section: Discussionmentioning
confidence: 99%
“…One small paediatric study showed significant correlation between plasma homocysteine rises in response to N2O and pre-operative vitamin B12 levels 46…”
Section: Methotrexate Use In Leukaemiamentioning
confidence: 99%